2006
DOI: 10.1002/ejlt.200600089
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antioxidants on butter in relation to storage temperature and duration

Abstract: The effect of antioxidants on butter in relation to storage temperature and durationThe effects of antioxidants on the oxidative stability of butter, under different storage time and temperature conditions, were evaluated. Natural (a-tocopherol) and synthetic (BHA and BHT) antioxidants were added to the butter samples at two concentrations (50 and 100 ppm) immediately after the butter samples were produced from the pasteurised sweet cream, after which they were kept in the dark at 4 and 220 7C for 6 months. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
4
19
3
Order By: Relevance
“…The highest TBA values were recorded at 90 days of storage in all the samples. These results were in agreement with Ozturk and Cakmakci [29] who indicated that the TBA values of the butter samples increased during storage. The principal components of Origanum acutidens essential oil at the flowering stages were carvacrol (64.58%), p-cymene (11.14%), borneol (2.88%) and linalool (2.28%).…”
Section: Resultssupporting
confidence: 95%
“…The highest TBA values were recorded at 90 days of storage in all the samples. These results were in agreement with Ozturk and Cakmakci [29] who indicated that the TBA values of the butter samples increased during storage. The principal components of Origanum acutidens essential oil at the flowering stages were carvacrol (64.58%), p-cymene (11.14%), borneol (2.88%) and linalool (2.28%).…”
Section: Resultssupporting
confidence: 95%
“…This emphasizes the ability of phenolics tested as antioxidants in butter, since they were active at 110 7C. Inhibition of butter oxidation by synthetic antioxidants [2] and by several extracts of plants has been reported by others [3,[9][10][11][12].…”
Section: Resultsmentioning
confidence: 69%
“…It is popular as cooking medium, while heating enhances lipid oxidation. However, there is scarce information regarding the improvement of the butter oxidative stability by natural and synthetic antioxidants [2].…”
Section: Introductionmentioning
confidence: 99%
“…ones has become popular as consumer awareness about chemical additives increased [5,6] . That is why researchers have been focusing on new natural sources that have high antioxidant activity and harmless for health to prolong shelf-life and to increase food stability [7][8][9] .…”
Section: Investigation Of Thementioning
confidence: 99%